A Consecutive Series Study of the Frequencies, Intensities, and Natural History of Symptoms Following COVID-19 Infection in Nepali Men - Shrestha, Deepak Sundar; Rahat, Arafat Mahamood; Sridevi, Parama; Chalise, Bimal Sharma; Rajbhandari, Sagar Kumar; Bastola, Anup; Bhandari, Parmananda; Ahamed, Sheikh Iqbal; Love, Richard R. (Journal of Nepal Health Research Council, 2023)
Background: In Nepal, approximately one million individuals, two-thirds men, have tested positive for COVID-19. The recovery picture from this infection is undescribed.Methods: At one major testing institution in Kathmandu, we attempted to contact men three-four months following documentation of a positive PCR Covid test. If the men contacted consented and reported that they had not completely recovered from their Covid infection, we then sought their answers about the presence and intensities of 23 symptoms.Results: Of 2043 consecutive test-positive men, we successfully contacted 1254 men/or family members. 14 men had died before our calls, and two reported having cancer or tuberculosis, providing 1238 individuals. 318 (25.7%) reported that they were unrecovered and 311 of these men were successfully interviewed. At a median of 3.5 months from diagnosis, 216 (17.4%) men reported fatigue, 153 (12.4%) pain, 134 (10.8%) difficulty remembering, 133 (10.7%) reduced physical activity, 114 (9.2%) shortness of breath, and 114 (9.2%) poor sleep. By 6 and 9 months, 108 (8.7%) and 55 (4.4%) of men respectively were still unrecovered.Conclusions: In this PCR Covid test-positive series of symptomatic men, recovery was significantly prolonged compared with other viral illnesses.Keywords: COVID-19; long-COVID; men; recovery; symptoms